PENGARUH INTENSITAS ASET TETAP, LEVERAGE DAN PROFITABILITAS TERHADAP TAX AVOIDANCE DENGAN PERTUMBUHAN PENJUALAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN SEKTOR PERTAMBANGAN DI BEI TAHUN 2017-2020 - Erni Ayu Mustikasari; Arif Hartono; Titin Eka Ardiana (Universitas Muhammadiyah Ponorogo, 2023)
This study aims to determine how the effect intensity of fixed asset, leverage, and profitability with tax avoidance. In addition, this study also aims to determine whether sales growth can moderate relation between intensity of fixed asset, leverage and profitability with tax avoidance. The population used in this study are mining sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2020. Collecting data in this study using documentation techniques obtained from the official website of the Indonesia Stock Exchange (IDX) through the link www.idx.co.id. The sample selection used purposive sampling technique. The analytical method used is multiple linear analysis using the statistical application of SPSS Version 26. The result of hypothesis testing indicate that the intensity of assets has no effect on tax avoidance, while leverage and profitability have negative effect on tax avoidance. Sales growth cannot moderate the relationship between fixed assets intensity and tax avoidance. However, sales growth can strengthen the relationship between leverage and tax avoidance and can weaken the relationship between profitability and tax avoidance.